Analisis Kebijakan Moneter dan Pengaruhnya Terhadap Perekonomian Indonesia Periode 2021-2022 - Karim Karim; Novita Rahmasari; Kasem Kasem; Rasidah Novita Sari (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
Indonesia's economic growth continues to increase and reaches inflation levels. As has happened in the last 2 years, there has been a quite drastic increase in inflation from 2021 of 1.56% and 2022 of 4.21%. This resulted in a decrease in rising inflation. Inflation is the impact of increasing or decreasing economic growth in a country. With increasing economic growth from trade activities or increased buying and selling along with increasing supply of businesses or producers, it can result in an increase in more buyers or consumers to shop, resulting in an increase in the prices of some good products or services market goods. One way to anticipate increasing inflation policies is that the government must control interest rates. Policies in this case must be made by the monetary authority in Indonesia, Bank Indonesia.